Words of triumph : the use of rhetoric in newspapers during the Reykjavík 2014 municipal election campaign - Ari Brynjólfsson 1989- (2015)
This thesis analyses the 2014 municipal elections in Reykjavík and explores the use of rhetorical devices by candidates and political parties during the last month of the election campaign in the three biggest newspapers in Iceland. A chapter on every participating party is provided with a discussion about its place in the political landscape before the campaign, a rhetorical analysis on campaign advertisements and an analysis of rhetorical devices used by top candidates. Ensuing the analysis is a comparison between the used rhetorics and an evaluation on their success by using the official election results.